Attitudes of Instructors Toward the Use and Implications of Artificial Intelligence in Online Higher Education - Alexa Schmitt; Rae Denise Madison; Robert Finkelmeier; Dawn Howell (The Pinnacle)
The purpose of this study was to assess the attitudes and perceptions of instructors toward the use and implication of artificial intelligence (AI) in online higher education spanning bachelor’s through doctorate level classroom instruction. 104 online higher education instructors were recruited through LinkedIn and the Colorado Technical University Teaching & Learning Center to complete a survey. Nonparametric statistical analysis was used to assess close-ended question responses and open-ended question responses were categorized. A significant difference in instructors’ concern for being displaced by AI in the next 2 years compared to the next 5 to 10 years was found at the bachelor’s level (p=0.04846). At the doctorate level, support for the use of AI in higher education was moderately correlated with concerns for being displaced by AI (rho=0.493, p=0.01058). Support for the use of AI in higher education by the instructor was moderately correlated with support for use of AI in the classroom by students (rho= 0.58199, p<0.001). Instructor support for allowing students to use AI in the classroom was not found to be dependent on the perception of the university employer providing instructors with the policies, procedures, and training to appropriately and ethically adapt to AI in the higher education classroom (p=0.7336). However, most participants recommended that the university develop strong policies regarding the use of AI. The findings indicate a positive preference toward the use of AI by both faculty and students, with some significant exceptions. Support and research toward adopting AI in the classroom are recommended.